Prevalence and socio‐demographic predictors of food insecurity among regional and remote Western Australian children - Stephanie Godrich; Johnny Lo; Christina Davies; Jill Darby; Amanda Devine (Australian and New Zealand Journal of Public Health, 2017)
Abstract Objective: Inequities can negatively impact the health outcomes of children. The aims of this study were to: i) ascertain the prevalence of food insecurity (FI) among regional and remote Western Australian (WA) children; and ii) determine which socio‐demographic factors predicted child FI. Methods: Caregiver‐child dyads (n=219) completed cross‐sectional surveys. Descriptive statistics and logistic regression analyses were conducted using IBM SPSS version 23. Results: Overall, 20.1% of children were classified as FI. Children whose family received government financial assistance were more likely to be FI (OR 2.60; CI 1.15, 5.91; p=0.022), as were children living in a Medium disadvantage area (OR 2.60; CI 1.18, 5.72; p=0.017), compared to High or Low SEIFA ratings. Conclusions: Study findings are suggestive of the impact low income has on capacity to be food secure. The higher FI prevalence among children from families receiving financial assistance and living in medium disadvantage areas indicates more support for these families is required. Recommendations include: ensuring government plans and policies adequately support disadvantaged families; increasing employment opportunities; establishing evidence on the causes and the potential impact of FI on children's health. Implications for public health: One in five children were FI, demonstrating that FI is an issue in Western Australia.